Comparative efficacies of ciprofloxacin, amoxicillin, amoxicillin-clavulanic acid, and cefaclor against experimental Streptococcus pneumoniae respiratory infections in mice. - Gisby, J (1991)
Experimental respiratory infections were established in mice by intranasal inoculation of Streptococcus pneumoniae. Inoculation of 10(7) CFU of either S. pneumoniae 1629 or S. pneumoniae 7 produced a fatal pneumonia in nontreated mice 2 to 3 days after infection. Oral therapy was commenced 1 h after infection and was continued three times a day for 2 days. The doses used in mice produced peak concentrations in serum and lung tissue similar to those measured in humans. Ciprofloxacin failed to eliminate either strain of pneumococcus from mouse lungs at any of the doses tested (40, 80, or 160 mg/kg of body weight) by the end of therapy (33 h). Mice that received ciprofloxacin at 160 mg/kg were clear of S. pneumoniae 7 5 days later, whereas persistence and regrowth of S. pneumoniae 1629 resulted in the death of 20% of animals treated with ciprofloxacin. Therapy with cefaclor (20 mg/kg) produced an effect similar to that of ciprofloxacin. In contrast, amoxicillin (10 and 20 mg/kg) and amoxicillin-clavulanic acid (10/5 and 20/10 mg/kg) were significantly (P less than 0.05) more effective in eliminating both strains of S. pneumoniae from the lungs by the end of therapy and, by 168 h, had prevented mortality in 80 to 100% of treated animals. The efficacy of ciprofloxacin against these experimental pneumococcal respiratory infections was poor, despite good penetration into lung tissue, and is a reflection of the low in vitro activity of the quinolone against S. pneumoniae, one of the most common pathogens in community-acquired pneumonia.